1979
DOI: 10.1002/1097-0142(197905)43:5<1636::aid-cncr2820430512>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Low dose fractionated whole body irradiation in the treatment of advanced non-Hodgkin's lymphoma

Abstract: Thirty-nine patients with advanced non-Hodgkin's lymphoma (38 patients with lymphocytic lymphoma and 1 patient with mixed lymphocytic and histiocytic lymphoma) were treated by fractionated low dose whole body irradiation (WBI) with a minimum follow-up of 8 months. Twenty-eight patients had no previous treatment and the other 11 patients were in relapse after previous chemotherapy or regional radiotherapy. There were 20 and 19 patients in stages 111 and IV groups, respectively. The majority of patients (31) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 9 publications
0
44
0
1
Order By: Relevance
“…Fractionated 0.1 to 0.15 Gy TBI has been applied in the clinical treatment of non-Hodgkin's lymphoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fractionated 0.1 to 0.15 Gy TBI has been applied in the clinical treatment of non-Hodgkin's lymphoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study, Chaffey et al (1976) reported that TBI doses smaller than 25 cGy were effective for lymphosarcoma tumor control, and Choi et al (1979) also reported that it is effective to use low doses of TBI in the treatment of advanced non-Hodgkin's lymphoma. Holder (1965) also recognized that multiple myeloma can be treated successfully by low doses of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…[28] The protocols were very similar. The Chaffey, et al 1976 trial used a 150 r LDR course with TBI doses of 15 r 2x/week for 5 weeks.…”
Section: Human Low Dose Radiation (Ldr) Cancer Immunotherapymentioning
confidence: 94%
“…The Chaffey, et al 1976 trial used a 150 r LDR course with TBI doses of 15 r 2x/week for 5 weeks. The Choi, et al 1979 trial also used a 150 r LDR course with TBI doses of either 15 r 2x/week or 10 r 3x/week for 5 weeks. In both studies transient low platelets requiring interruption of scheduled therapy occurred in 35-40% of patients, irrespective of 10 r or 15 r dose schedule.…”
Section: Human Low Dose Radiation (Ldr) Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation